Hermeneutic Phenomenology: Debates on Uniformity and Diversity - Acharya, Binod Kumar (Haimaprabha, 2024)
This article explores hermeneutic phenomenology as the advocacy on diversity and uniformity. While interpreting the phenomena both individual insight and cultural backup pay equal contribution. The absence of the one limits the meaning of the phenomena. Although Descartes takes consciousness a priori, he does not refuse the significance of the body. The society stays dominant for Max. However, how could his society exist in the absence of individual. The more they use different rhetoric, the more they discuss about form and content, competence and performance, superstructure and base. Although Husserl insists on bracketing to avoid unnecessary influence from others, it is impossible to stay away from culture and society. I have used hermeneutic phenomenology to look at their arguments. The more they seem specific, the more they stand biased. I disagree on the polarity of these philosophers. Moreover, hermeneutic phenomenology has multiple dimensions. It is inclusive in nature because we could not deny the plurality of things. Additionally, this study focuses on the way diversity and uniformity manifested in hermeneutic phenomenology and how these philosophers refuse the prevalence of the uniformity.